Picture archiving and communication systems in digital cytology - Sandra Morelli; Mauro Grigioni; Maria Rosaria Giovagnoli; Simone Balzano; Daniele Giansanti (Istituto Superiore di Sanità, 2010)
The paper describes a fundamental feature of digital cytology relevant to the implementation of the technology in the hospital net services: the electronic recording of the virtual slides (VS) in the hospital information system (HIS) through a picture archiving and communication system (PACS). Starting from the digital cytology (D-CYT) state of art and considering the most important products in the field, particular attention has been devoted in this review to the comparison with the digital radiology (D-RAD). Two main indications emerged from the study: 1. there is not a standard in the digital files relevant to the virtual slides in D-CYT, while in D-RAD the standard digital imaging and communications in medicine (DICOM), introduced by the National Electrical Manufacturers Association (NEMA), has been adopted from several years; 2. the PACS in D-CYT are not standardized from manufacturers. The study makes a proposal of a useful software architecture to improve the PACS integration for D-CYT applications, with potentialities in the HIS.